TOTEMISME PADA OBJEK IREZUMI DALAM SERI GIM YAKUZA: TATO SEBAGAI BEBAN PSIKOLOGIS - Harahap, Aqiilah Bilqiis Salsabiil; Susanto, Dwi; Mibtadin, Mibtadin; Ardianto, Deny Tri (UI Scholars Hub, 2023)
Totemism is a belief in an animal or plant’s guiding spirit that is linked to a person’s character and destiny. Totemism manifests itself in tattoos as body decoration and symbols of hope, such as Yakuza tattoos (irezumi). This research aims to reveal the representation and meaning of totemistic irezumi worn by three Yakuza characters (Kazuma Kiryuu, Akira Nishikiyama, and Goro Majima) in two Yakuza-themed game series: Yakuza 0 (2015) and Yakuza Kiwami 1 (2016). These games provided the primary data in the form of images and conversations. Ricoeur’s hermeneutic theory was applied to examine the data, along with qualitative descriptive and interpretative methods. Analysis revealed differences between the meaning of tattoos shown in the Yakuza games and those existing in the real world. Kiryuu’s dragon tattoo represents the burden of responsibility; Nishiki’s koi tattoo represents the burden of being a great individual; and Majima’s tattoo represents an emotional burden. Thus, the entities shown in those irezumi can be said to represent psychological burden and influence their bearers’ as personal totems.